Assessment and treatment activities for children, adolescents, and families : practitioners share their most effective techniques - Lowenstein, Liana, 1965- (Toronto : Champion Press, 2008)
Contains instructions and resources for activities to help children who have been referred for therapy maintain interest and motivation during the process, including assessment and treatment interventions, and providing activities that address key emotional and behavioral competencies, with listings of recommended ages, goals, and materials needed for each activity.
Includes bibliographical references.
Keywords: Child psychotherapy; Play therapy; Family psychotherapy